Innovation in the Management of SMEs in the Service Sector in Poland - Robert Nowacki; Marcin W. Staniewski (Amfiteatru Economic Journal, 2012)
The present study focuses on the issue of innovation among small and medium-sized enterprises (SMEs), which constitute the lifeblood of economic growth. The power of this lifeblood depends on the level of innovativeness of these enterprises insofar as SMEs consider innovation their main operational strategy for gaining a competitive advantage over large companies. Innovation accrues various economic advantages for SMEs that may not be overlooked in the management process. The authors of this paper therefore analyze the awareness and use of innovative solutions in the management process of SMEs operating within the service sector in Poland. The research was conducted in 2009 to 2010 through direct face-to-face interviews with 608 top managers.
Keywords: D00; 330; innovation; management; SME; service sector; Poland